Industrialisation in a small grain economy during the First Globalisation: Bulgaria c. 1870–1910 - Martin Ivanov; Michael Kopsidis (The Economic History Review, 2023)
In Bulgaria the share of secondary production in GDP remained constantly low between c. 1870–1910. To explain the country's exceptionally weak growth, we use endogenous and unified growth theory. Gerschenkron and Palairet blame a self-sufficiency-oriented peasant economy for rising labour and raw material costs in industry, which destroyed the competitiveness of Bulgarian manufacturing and prevented industrialisation. We refute the existence of any long-lasting cost increases in industry after 1878. Quite the opposite was true: the expansion of Bulgaria's secondary sector was restricted by detrimental changes on the demand side, for which peasants were not responsible. Recent research claims that, around 1910, Bulgarian textile production was significantly lower than in 1870. Our study brings to light new data and information that clearly disproves this view. Until around 1910, a booming modern manufacturing sector more than replaced the country's proto-industries' textile outputs, which had plummeted dramatically during the early years of the newly founded Bulgarian state. However, as the rise of modern manufacturing in textile production coincided with the decline of the entire large sector of traditional manufacturing, secondary production as a whole stagnated.
Keywords: 330; agriculture; Bulgaria; first globalisation; foreign trade; industrialisation; nineteenth century; textile industry